Pengembangan Keterampilan Sosial Anak Usia Dini Melalui Permainan Tradisional Madura - Diana Vidya Fakhriyani (Universitas Trunojoyo Madura, 2018)
A person should have the social skills to be able to interact with his environment. Social skills should be developed at an early age, because at this early age individuals have learned to socialize with other individuals. Therefore, social skills can be developed from an early age, so that children can play a role in socializing with his environment. Development of early child social skills can be done with many things, one of Madurese traditional game. The traditional game of Madura is a game in Madura, which in fact is currently largely abandoned. There are various kinds of Madurese traditional games, where in this article there are games Kocheng-tekos and bhisek as one of the development alternatives that can be applied in order to develop social skills for early childhood.